(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
The process of globalization has a significant impact on the education system, requiring new approaches to human capital development. This article analyzes reforms aimed at improving the quality of education and aligning it with market demands. Additionally, it highlights pressing issues in developing the education system through the use of innovative methods and modern technologies. The paper explores the interconnection between education and the economy, offering strategic recommendations for enhancing human capital development.